2012
DOI: 10.4028/www.scientific.net/amm.152-154.1207
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Creep Properties of the Cast Magnesium Alloy

Abstract: Currently most commercial magnesium alloys are based on the Mg-Al system and it is reasonably well developed. Although the Mg-Al based alloy system has excellent castability and adequate ambient temperature mechanical properties, it shows poor creep resistance. Therefore, our group has focused on finding the way to improve the creep properties of Mg alloys. This paper presents a brief summary of the research achievements in this area recently made by AFML(Advance Functional Materials Lab in PNU, Korea). The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…As a promising alloy system, Mg-Zn-Al Series alloys, especially Mg-10~12wt.%Zn-2~4wt.%Al alloys were investigated. Results show that the creep resistance of these ZA alloys containing 4wt.%Al are significantly better than those of AZ91 with comparable tensile properties, thus make them potentially good candidates for applications at elevated temperature [2,3]. However, effects of Zn content on the microstructures and properties, especially creep resistance of these ZA alloys containing 4wt.…”
Section: Introductionmentioning
confidence: 99%
“…As a promising alloy system, Mg-Zn-Al Series alloys, especially Mg-10~12wt.%Zn-2~4wt.%Al alloys were investigated. Results show that the creep resistance of these ZA alloys containing 4wt.%Al are significantly better than those of AZ91 with comparable tensile properties, thus make them potentially good candidates for applications at elevated temperature [2,3]. However, effects of Zn content on the microstructures and properties, especially creep resistance of these ZA alloys containing 4wt.…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium alloys are emerging as potentially good candidates for numerous applications, especially in automotive, aerospace and electronic industry [1]. In the early 1970s, It was reported that alloys with high zinc and low aluminum(Mg-Zn-Al Series alloys) could meet the property requirements so as to be an alternative to the presently used Mg-Al based alloys [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…However, inferior high temperature mechanical properties of conventional Mg-Al system alloys, such as AZ91 and AM60, limit the potential utilization of these alloys in important parts due to the low melting point of the intermetallic phase β phase (Mg17Al12) in the microstructure, which is prone to soften at above 120℃ [1].…”
Section: Introductionmentioning
confidence: 99%